2005
DOI: 10.1093/molehr/gah161
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone receptor expression in human decidua and fetal membranes before and after contractions: possible mechanism for functional progesterone withdrawal

Abstract: In humans, progesterone levels are sustained before the onset of labour. Therefore, the mechanism for parturition that has been proposed for humans is 'functional' progesterone withdrawal. Immunohistochemical staining for the progesterone receptor (PR) was positive in the decidua with a decline after contractions began. Western blot analysis revealed a number of PR isoforms expressed in the decidua, with the PR-B form being dominant. After contractions began, all PR isoforms decreased sharply. PR-B and PR-A de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
64
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(77 citation statements)
references
References 36 publications
9
64
4
Order By: Relevance
“…There is also evidence that inflammation via NF-κB can reduce P 4 effectiveness and PGF 2α increases PR-A expression without affecting PR-B expression (69, 70). In addition, several studies reported that human labor is associated with reduced decidual expression of PR (71)(72)(73). Taken together, the evidence indicates that P 4 signaling in the context of myometrial contractility in human parturition requires further investigation.…”
Section: Figurementioning
confidence: 76%
“…There is also evidence that inflammation via NF-κB can reduce P 4 effectiveness and PGF 2α increases PR-A expression without affecting PR-B expression (69, 70). In addition, several studies reported that human labor is associated with reduced decidual expression of PR (71)(72)(73). Taken together, the evidence indicates that P 4 signaling in the context of myometrial contractility in human parturition requires further investigation.…”
Section: Figurementioning
confidence: 76%
“…In biopsies of cervices from peripartum women, concentrations of progesterone receptor protein decreased at term to 25% of the level found in nonpregnant women [10]. Other recent findings suggest that PGF 2alpha promotes the expression of inhibitory progesterone receptor isoforms in myometrium from parturient women [11,12]. Thus, in rodents, as in primates, actions of PGF 2alpha may contribute to a reduced efficacy of progesterone and promote processes that enhance uterine contractility in preparation for parturition.…”
Section: Introductionmentioning
confidence: 92%
“…Both PGRA and PGRB may activate different sets of genes, even within the same cell, revealing the enormous complexity of progesterone-dependent activation in the target cell (Graham & Clarke 2002, Alfaro et al 2012. This suggests that changes in the expression of PGR isoforms could regulate the biological activity of progesterone, resulting in functional hormone withdrawal at the ovarian level, under unchanged progesterone serum concentrations (Schams et al 2003, Amrozi et al 2004, Goldman et al 2005.…”
Section: R253mentioning
confidence: 99%